(untitled) (JURNAL GEOCELEBES, 2023)
This study specifically aims to identify coastal abrasion as seen from the coastline shift, from 1989 to 2020 in Pesisir Utara Sub-district and Lemong Sub-district, Pesisir Barat Regency, Lampung Province, by interpreting remote sensing data. The data used are Landsat satellite imagery for 1989, 2000, 2006, and 2020. Landsat satellite imagery are corrected by radiometric and geometric correction. The geometric correction is registered to Landsat imagery in 1989. The corrected satellite imagery is digitized for the coastline. The results of the digitized coastline were then overlaid, then the coastline shift was calculated from 1989 to 2020. The coastline shift calculation was carried out at 16 locations in Pesisir Utara Sub-district and Lemong Sub-district. The results of calculations at 16 sample locations show that there has been a shift in the coastline due to coastal abrasion from 1989 to 2020 of 2.0 m/yr. For areas where the coastal conditions are rocky and there are shallow rocks in front of it, the coastline shift is only small, such as in the cape area before Walur Village. This coastline shift was also evidenced by direct checking of the area and asking local residents, the results showed that the overall shift of the coastline was caused by coastal abrasion.